A Comparative Study on Thermal and Microstructural Properties of Different Types of NiMnGa Magnetic Shape Memory Alloys - Kok, Mediha; Aydogdu, Yildirim (Springer, 2013)
In this study, the thermal and microstructural properties of the first and second types of NiMnGa alloys were compared by using XRD and DSC measurements. According to the XRD measurements, these alloys exhibits both a martensite phase with tetragonal structure and a gamma phase. The results show that the second type of NiMnGa alloy has a higher intensity of the main peak, with indices of (222), than the first type of FSMA has. This means that the crystal structure of the second type of alloy is more ordered. Similarly, the DSC curves of the two types of alloys show some differences. When heating and cooling, there are two peaks in the DSC curve of the first type of alloy, while the second type of alloy has only one peak. For the first type of alloy, the initial peak is an indicator of martensitic transformation and the other peak is that of Curie temperature. For the second type of alloy, the major peak shows the martensitic transformation temperature. The highest enthalpy change and activation energy are seen for the second type of alloy.
Keywords: Ferromagnetic shape memory alloys; NiMnGa; First type; Second type